PENGARUH AUDIT INTERNAL TERHADAP PENGUNGKAPAN KELEMAHAN PENGENDALIAN INTERNAL PADA UNIVERSITAS MUHAMMADIYAH PAREPARE - Khaerunni’mah, Khaerunni’mah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of internal audits on the disclosure of weaknesses in the internal control system at the University of Muhammadiyah Parepare. The expected benefit from the results of this research is to add a reference to the influence of internal audits on the disclosure of internal control weaknesses within the university and as reference material for similar research conducted in the future. The sample in this study were staff or employees at the Muhammadiyah University of Parepare, namely the Chancellor, Vice-Chancellor, SPI, Bureau, Institutions, and Faculties. This research is descriptive quantitative research. The data sources used are primary data and secondary data. The data collection techniques used were questionnaires and interviews. The data analysis technique used was SPSS 26. From the results of the questionnaires distributed as many as 31 with a total of 19 questions declared valid. The results of this study indicate that internal audit has a significant effect on the disclosure of internal control weaknesses.